EFFECT OF FUCOIDAN ON B16 MURINE MELANOMA CELL MELANIN FORMATION AND APOPTOSIS - Wang, Zhi-Jiang; Wei, Xu; Liang, Jian-Wen; Wang, Cai-Sheng; Kang, Yani (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background:Fucoidan is a complex sulfated polysaccharide extracted from brown seaweed and has a wide variety of biological activities. It not only inhibits cancer cell growth but also inhibits tyrosinase in vitro. Therefore, it is of interest to investigate the effect of fucoidan on B16 murine melanoma cells as the findings may provide new insights into the underlying mechanism regarding the inhibition of melanin formation by fucoidan. In the present study, we aimed to investigate the anti-melanogenic effect of fucoidan and its inhibitory effect on B16 cells. Materials and Methods: The influence of fucoidan on B16 melanoma cells and cellular tyrosinase was examined. Cell viability was examined by the cell counting kit-8 assay. Cellular tyrosinase activity and melanin content were determined using spectrophotometric methods and protein expression was analyzed by immunoblotting. Morphological changes in B16 melanoma cells were examined by phase contrast microscopy and apoptosis was analyzed by flow cytometry. Results: In vitro studies were performed using cell viability analysis and showed that fucoidan significantly decreased viable cell number in a dose-response manner with an IC50 of 550 ±4.3 μg/mL. Cell morphology was altered and significant apoptosis was induced when cells were exposed to 550 μg/mL fucoidan for 48 h. Conclusion: This study provides substantial evidence to show that fucoidan inhibits B16 melanoma cell proliferation and cellular tyrosinase activity. Fucoidan may be useful in the treatment of hyperpigmentation and as a skin-whitening agent in the cosmetics industry.